Circularly polarized rectangular dielectric resonator antenna excited by an off-set conformal metal strip - U. Illahi; J. Iqbal; M. I. Sulaiman; M Alam; M. S. Mazliham; M. H. Jamaluddin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A rectangular dielectric resonator antenna (DRA) has been excited by an off-set single conformal metal strip. By using such excitation technique two degenerate resonant modes, TExδ11 and TEy1δ1 of the rectangular DRA have been excited to achieve circular polarization (CP). A CP bandwidth of ~ 5.2% in conjunction with a wide impedance matching bandwidth of ~ 54% has been provided by the proposed DRA configuration. The antenna design has been simulated using computer simulation technology (CST). Antenna prototype has been built to verify the impedance matching bandwidth. Far field parameters have been optimized and verified using two simulation techniques in CST i.e. finite integration technique (FIT) and finite element method (FEM). A good agreement between the simulated and measured result has been observed for S11. Similarly a very good resemblance between the far field results from FIT and FEM have been demonstrated.